THE REPRESENTATION OF POWER AND SOCIAL INEQUALITY IN “THE BEGGAR AND THE KING” - Laila Nur Afriani (Conscientia - Journal on Language, Literature, and Culture, 2026)
Literature is widely recognized not only as a form of artistic expression, but also as a medium that reflects social realities, including issues of power, inequality, and class relations. In many literary works, especially drama, these issues are presented through characters, dialogue, and conflict, allowing readers to see how social structures operate within a narrative. Drama, in particular, offers a direct representation of human interaction, making it an effective medium to explore how authority is exercised and how marginalized voices are portrayed. Therefore, analyzing drama can provide a deeper understanding of how social conditions and power relations are constructed and represented in society.